Locked In : One man's miraculous escape from the terrifying confines of Locked-in syndrome /: One man's miraculous escape from the terrifying confines of Locked-in syndrome. (2014) - Marsh, Richard, Hudson, Jeff; Hudson, Jeff
No abstract available